The Influence of E WOM Brand Image Product Features and Product Price on Purchase Intention for the Samsung Galaxy S23 Smartphone in Indonesia - Frintika, Marani Tamelin; Rachmawati, Indira (Manajemen dan Kewirausahaan, 2023)
The rapid growth of technology has brought advances in information technology that can be easily accessed and has had a positive impact on all aspects especially smartphones One of the well known smartphone companies in Indonesia is Samsung Samsung is a smartphone that is favored by the public and occupies the position of Top Brand Award in Indonesia but in recent years the market share of Samsung smartphones has decreased The objective of this study is to ascertain electronic word of mouth brand image product features product prices and purchase intentions on Samsung Galaxy S23 smartphones The research method used is the quantitative method The population and samples used in this study are people in Indonesia who have seen online reviews of the Samsung Galaxy S23 smartphone and are interested in or motivated to make purchases on the Samsung Galaxy S23 smartphone The sampling technique used is the purposive sampling method by distributing questionnaires to 385 respondents Based on this research it is recommended that the Samsung Galaxy S23 smartphone pay attention to the variable production price The company can review the price offered to match the competitive market and the features it has to increase purchase intention< em>< p>